Magnitude and associated factors of adverse perinatal outcomes among women with oligohydramnios at 3rd trimester at University of Gondar comprehensive specialized hospital, North West Ethiopia - Molla, Mezigebu; Mengistu, Zelalem; Tsehaye, Winta; Sisay, Getasew (Frontiers in Global Women's Health, 2023)
Background: Oligohydramnios is a pregnancy condition characterized by a low amniotic fluid volume. Based on ultrasound measurement, it is defined as a single maximum vertical pocket of liquor less than 2 cm or a summation of four quadrants of vertical pockets of liquor measurement less than 5 cm. It is associated with multiple adverse perinatal outcomes (APO) and complicates 0.5-5% of pregnancies. Objective: To assess the magnitude and associated factors of adverse perinatal outcomes among women with oligohydramnios in the 3rd trimester at the University of Gondar Comprehensive Specialized Hospital, North West Ethiopia Methods: Institution-based cross-sectional study was employed from April 1 to September 30, 2021, in which 264 participants were involved. All women with oligohydramnios in the 3rd trimester who meet the inclusion criteria were included. A semi-structured questionnaire was used for data collection after being Pre-tested. Collected data was checked for completeness; clarity was then coded and entered using Epi data version 4.6.0.2 then exported to STATA version 14.1 for analysis. Result: The magnitude of APO was 46.6% (95%CI, 40.5-52.7%). Null parity (AOR= 2.2, 95%CI [1.2-4.2]), presence of hypertensive disorders of pregnancy (HDP) (AOR=4.9, 95%CI [2.0-12.1]) and presence of intrauterine growth restriction (IUGR) (AOR=8.4, 95%CI [3.5-20.2]) were found to be predictors of APO. Conclusion: Third-trimester oligohydramnios is associated with APO. The presence of HDP, IUGR, and being nulliparous were predictors of APO.